Existing theories of concrete spalling and test methods relating to moisture migration patterns upon exposure to elevated temperatures – A review. (June 2022) - Kannangara, Thathsarani; Joseph, Paul; Fragomeni, Sam; Guerrieri, Maurice
Abstract: The present paper reviews some recent research on concrete spalling theories and existing test methods of moisture migration patterns that occur when concrete is exposed to elevated temperatures. Experimental investigations on these systems in fire conditions are not as extensively conducted as under normal temperature conditions. Therefore, only a few representative experimental procedures are discussed in the paper. A summary of small-, medium- and large-scale experimental tests where water pooling was evident is also presented. This is then presented in relation to the design recommendations that are based on previously discussed experiments. Finally, some future perspectives on the subject matter are also presented.